Characterizing clusters of gentrification in metro Atlanta, 2000 to 2016. (December 2021) - Corrigan, Anne E.; Curriero, Frank C.; Linton, Sabriya L.
Abstract: Gentrification can drive residential displacement and exacerbate social inequities; however, no consensus about such impacts exists because gentrification definitions vary, and methods lack spatial statistics. Here, gentrification scores were calculated for census tracts in the Atlanta metropolitan area, 2000–2016. Spatial autocorrelation of gentrification was assessed, and spatial cluster detection identified hotspots and coldspots of gentrification. Sub-analyses evaluated the impact of time period (before/after 2010) and conceptualization of gentrification (purely economic changes or a combination of changes in economic, racial, and age composition) on the size and location of clusters. Extreme gentrification occurred around downtown Atlanta, while southern and eastern reaches experienced economic decline and decreases in older and non-Hispanic White residents. Leveraging spatial statistical analysis and examining gentrification hotspots across metrics, this study establishes critical understanding of historic gentrification in Atlanta and lays the groundwork to further examine gentrification's impact on the wellbeing of residents and communities to inform urban planning decisions to advance equity. Highlights: Spatial cluster detection analysis was used to identify gentrification in Atlanta. Atlanta gentrification showed extreme spatial autocorrelation. One hotspot of gentrification and two coldspots of gentrification were identified. Size of the hotspot varied by time period and inclusion of race/ethnicity and age. Coldspots' size and location varied by time period and inclusion of race and age.